Utilização das técnicas de caracterização do estado sólido para identificação de adulterantes farmacêuticos em emagrecedores naturais - Vieira, Renata dos Santos (2020)
Due to the impacts of obesity and overweight, it is often considered necessary, among the treatment alternatives, the use of drugs. On account of its natural origin, the use of herbal medicines to treat obesity and overweight has been increasing. However, even with regulations from health authorities, the growing trade in pharmaceutical products on the Internet has facilitated the entry of adulterated products that are sold as 100% natural, with miraculous promises of effective treatment in the short term. Therefore, it is urgent to detect adulterated formulations through fast, low-cost and sensitive procedures to detect their active ingredients or potential impurities and adulterants. However, most of the analytical methods used routinely are destructive, have high cost and complexity and require a long period of time for analysis and / or an excessive quantity of organic solvents. Thus, in view of the above and the environmental impacts and in compliance with the principles of Green Chemistry, the present study proposes to minimize and / or eliminate the use of harmful solvents, use of direct analytical techniques and use of a minimum amount of samples to determine pharmaceutical adulterants in weight loss products sold as natural. The solid state characterization techniques were evaluated in this work: optical microscopy, X-ray diffraction, vibrational spectroscopy and thermal analysis.